Receipt of Prescribed Controlled Substances by Adolescents and Young Adults Prior to Presenting for Opiate Dependence Treatment. (17th February 2013) - Matson, Steven C.; Bentley, Cathleen; Hughes Dughman, Vicki; Bonny, Andrea E.
Abstract : Purpose . The objective of this study was to document the number of controlled substance prescriptions filled by adolescents and young adult patients in the 2 years prior to presentation for opiate dependence treatment. Methods . Opiate-dependent youth (N = 125 ) presenting to our Medication-Assisted Treatment for Addiction program from January 1, 2008 to June 30, 2010 were identified via electronic medical record. Subjects were further classified based on their opiate use as dependent to heroin-only, prescription (Rx) opiate-only, or combined heroin + Rx opiate only. The Ohio Automated Rx Reporting System (OARRS) was used to identify each subject's controlled substance prescription history. Negative binomial regression was used to examine the relationships between patient characteristics and the total number of prescriptions filled. Results . Twenty-five percent of subjects had filled ≥6 prescriptions, and 15% had filled ≥11 prescriptions. The mean number of prescriptions filled was 5 (range: 0–59). Thirteen percent had filled ≥6 opiate/narcotic prescriptions, and 8% had filled ≥11 prescriptions. Conclusions . A subset of opiate-dependent youth had filled multiple opiate/narcotic prescriptions providing some evidence that physician-provided prescriptions may be a source of opiate abuse or diversion for a minority of opiate-dependent adolescents and young adults.